Genetic Algorithm with Fast Greedy Heuristic for Clustering and Location Problems - Kazakovtsev, Lev A.; Antamoshkin, Alexander N. (Informatica, 2014)
Authors propose new genetic algorithm for solving the planar p-median location problem and k-meansclustering problem. The ideas of the algorithm are based on the genetic algorithm with greedy heuristicfor the p-median problem on networks and information bottleneck (IB) clustering algorithms. The proposedalgorithm uses the standard k-means procedure or any other similar algorithm for local search. Theefficiency of the proposed algorithm in comparison with known algorithms was proved by experiments onlarge-scale location and clustering problems.